2013
DOI: 10.1155/2013/238528
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of MTHFR Associated with Higher Relapse/Death Ratio and Delayed Weekly MTX Administration in Pediatric Lymphoid Malignancies

Abstract: Backgrounds. Outcome of childhood malignancy has been improved mostly due to the advances in diagnostic techniques and treatment strategies. While methotrexate (MTX) related polymorphisms have been under investigation in childhood malignancies, many controversial results have been offered. Objectives. To evaluate associations of polymorphisms related MTX metabolisms and clinical course in childhood lymphoid malignancies. Method. Eighty-two acute lymphoblastic leukemia and 21 non-Hodgkin's lymphoma children wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
(62 reference statements)
0
22
0
2
Order By: Relevance
“…Hepatotoxicity was analyzed in 7 studies, only Fukushima et al28 showed significant results in their cohort of children, which as previously mentioned, mixed 82 ALL patients and 21 NHL patients. In this study, 1298CC genotype patients presented a lower hepatic toxicity risk comparing to the 1298AA genotype patients.…”
Section: A1298c Polymorphism Analysismentioning
confidence: 97%
See 4 more Smart Citations
“…Hepatotoxicity was analyzed in 7 studies, only Fukushima et al28 showed significant results in their cohort of children, which as previously mentioned, mixed 82 ALL patients and 21 NHL patients. In this study, 1298CC genotype patients presented a lower hepatic toxicity risk comparing to the 1298AA genotype patients.…”
Section: A1298c Polymorphism Analysismentioning
confidence: 97%
“…From them, only 5 found significant associations with toxicity, but with contradictory results: 2 studies related the T variant allele to a decrease in toxicity risk,24,25 whereas the other 3 associated it to increased risk (Table 1). 2628…”
Section: C677t Polymorphism Analysismentioning
confidence: 99%
See 3 more Smart Citations